Intra-party democracy in Nigerian political parties: A historical survey - Abdel Salam, El Fatih Abdullahi; Musa, Yahaya Yuusuf (2017)
In modern societies, the use of the concept of intra-party democracy in carrying out the normal business of political parties, especially with regards to primary elections, is never to be compromised and, therefore, invaluable. Internal democracy in most, if not all democracies is supposed to operate within the framework of law, openness and ethics in carrying out responsibilities to organizations, groups or the society at large. Selecting who represents a party during the election can be described as one among other major activities of both political parties in advanced political system as well as emerging ones. This paper examines party politics and the conduct of intra-party democracy and candidate selection in perspectives in the history of political parties and political system in Nigeria since its independence. Specifically, the paper reviews issues of political parties in Nigerian democracy, party leadership, decision-making and candidate selection in historical perspective within the framework of internal party politics. It is found that in new democracies, such as Nigeria, parties are still at their infancy stage and many were formed along ethnic, tribal or even, in some cases, religious lines. In short, parties reflect the seeming socio-cultural and political cleavages in the society. Another issue with regards to the political process or democratization of party politics is the question of money induced politics and godfatherism. It has dominated the fabrics of the political parties in the country.